Analisis Kebijakan dan Kepemimpinan Guru Dalam Menghadapi Kurikulum 2013 Era Globalisasi - Andriana Sofiarini; Elya Rosalina (Universitas Pahlawan Tuanku Tambusai, 2021)
Basically, the change of the curriculum is to adapt to the progress of the times. Changes from the previous curriculum to the 2013 curriculum caused many groups, especially teachers to be less prepared to accept these changes. A challenge for teachers to be able to adapt to the times that are adapted to the 2013 curriculum.The research objective is to analyze the role of teachers in the 2013 curriculum in the globalization era. The research method used in this research is descriptive qualitative method. The source of research data used is the result of direct observation by researchers as observers of the world of education at the school level. In addition to sources of observation, researchers use reference sources in the form of scientific journals and books that are relevant to the research being studied. The results of the study were: 1) The role of teacher leadership, namely a teacher in the world of education, how to be a good leader and responsible for the progress of students in school. Teacher leadership as a facilitator must be implemented to students in accordance with the needs of students in learning, 2) Analysis of the Role of Teachers on the 2013 Curriculum in the Globalization Era, namely teachers in this era of globalization must be able to bring themselves so as not to lag behind the times. The 2013 curriculum that has been implemented in schools must be used by teachers to improve themselves with various activities that support student education in schools. As a facilitator, the teacher must be able to set a good example for students. In addition, teachers must be able to use the technology used in education.